Transforming human gait for signature signals characterization - Atika, Arshad; Ismail, Ahmad Fadzil; Khan, Sheroz; Alam, A. H. M. Zahirul; Rumana, Tasnim; Haider, Syed Samnan; Shobaki, Mohammed M.; Shahid, Zeeshan (2013)
An integrated wireless inductive sensor is reported based on a system for monitoring human movement and body size. The proposed system senses the presence of human beings using electromagnetic field by making use of basic inductive coupling approach, hence analysing the performance of human monitoring. The amalgamation of the integrated system proposed will help in providing better services to the elderly people resided in healthcare centres. The developed sensing system is of low cost, flexible, robust, and easily implantable and capable of inductive sensing through marking signature waveforms as a result of human movements.